A "experiência Laborarte" (1972-1980): a importância dos seus experimentalismos musicais e sua possível utilização em sala de aula - Gonçalves, Ivan Veras (2016)
The paper focuses on the historical and artistic and educational aspects, the situation of music, education and culture it was in the city of Sao Luis in the years before the creation of the Artistic-LABORARTE Expression Laboratory, a theatrical group an impressive track record, in order to situate the reader about the motivation for its creation. Address the musical and theatrical experimentalism important performed in LABORARTE and influenced the changes in the urban music of Maranhão, as well as all research procedures that were implemented in the group Sound Department-Laboratory. From this research we intend to focus on the teaching side of LABORARTE and propose the analysis of their research in the music area, and propose their possible reproduction in the classroom through interdisciplinary workshops that enable the reproduction of the "Experience LABORARTE" as a tool for teaching music.